Tables for near vision examination in low vision patients - T. S. Egorova (Российский офтальмологический журнал)
Purpose: to design methods and algorithms of technical means selection for near visual work in low vision patients. We propose tables to measure near vision acuity ranging from 0.01 to 0.8, with test character sizes varying in logarithmic progression with 1.26 denominator. The tables help determine the minimal size of readable font = the reading threshold and magnification degree needed to ensure the reading of a normal font. To choose the optimal magnifier, a quantitative criterion was chosen — the reading rate. Due to these methods we were able to recommend the most effective technical means of rehabilitation for monocular or binocular use depending on the reading threshold, reading rate, the presence of ophthalmic pathologies and the patient’s age.